What interpretation service are cultural tourists willing to pay for? A choice-experiment approach for cultural heritage sites in China. (March 2023) - Zhao, Weiyan; Chan, Chung Shing
Abstract: This study aims to explore tourists' willingness to pay (WTP) for interpretation through measuring marginal willingness-to-pay for interpretive attributes, identifying influencing factors of WTP, and illustrating heterogeneity in tourists' preference. Choice experiment was applied to this study with 536 valid online questionnaires from respondents in China. Results revealed that respondents were willing to pay the highest price (RMB134) for a short service length. Short service length, interpretive style, content about architectural style of heritage, and distinctive local cultures positively influenced WTP, while sense of humor, interactivity, knowledge of heritage conservation and long service length negatively influenced WTP. Besides, four segments of tourists with different preference patterns for interpretive attributes were identified. This study provides practitioners with useful information about design and marketing of interpretation in cultural heritage sites. Highlights: Interpretive attributes have different impacts on tourists' willingness-to-pay. Tourists are willing to pay the highest price for a short service length. Tourists' preferences for interpretation are heterogeneous. Entertainment preferred group is a primary market segment in Chinese cultural heritage sites.